Open Versus Sealed-Bid Auctions: Testing for Revenue Equivalence under Singapore's Vehicle Quota System - KOH, Winston T. H. (Institutional Knowledge at Singapore Management University, 2003)
Using data from the auction of vehicle quota licenses in Singapore, we study if revenue equivalence holds when the auction format was switched from a sealed-bid format (May 1990 to June 2001) to an open bidding format since July 2001. Our econometric analysis indicates the change in auction format led to a change in bidding behavior. On average, the quota license premium under the open bidding format is about US$1,000 (about 7.5% of the Category E license price in June 2001) lower, compared to the forecast level that would have prevailed if there had been no change in the auction format.